PELAKSANAAN PROMOSI PADA RAMAYANA BALLET PRAMBANAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Agraprana, Abel; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to determine the implementation of promotions carried out by a company to introduce the products or services it has. This research was conducted in Prambanan District, Sleman Regency, Yogyakarta Special Region. This research uses a qualitative descriptive method in which the researcher explains the topic of the problem and draws conclusions. Ramayana Ballet Prambanan has carried out promotions with the promotional mix used, namely advertising, personal selling, sales promotion, public relations and direct marketing. Thus, the implementation of promotions is expected to help increase sales, improve image and also increase profits for individuals and organizations. Keywords: Implementation, Promotion, Ramayana Ballet Prambanan